Heart Rate Variability in Dynamics of Aging in Rats on Background of Repeated Extreme Rhythmic Cryoexposures - Rudnyeva, Yuliya V.; Babiychuk, Vladislav G.; Chernyavskaya, Elena A.; Kulik, Vladimir V. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):169.